Identifying solid luminogens through gold-catalysed intramolecular hydroarylation of alkynes - Shaikh, Aslam C.; Shalini, S.; Vaidhyanathan, Ramanathan; Mane, Manoj V.; Barui, Ayan Kumar; Patra, Chitta Ranjan; Venkatesh, Yeduru; Bangal, Prakriti Ranjan; Patil, Nitin T. (European Journal of Organic Chemistry, 2015)
The identification of a new class of luminogens based on pyrrolo-quinoxaline embedded coumarin (PQC) structures is reported. The reaction relies on the gold-catalyzed hydroarylation reaction of appropriately substituted aryl alkynoates that produces molecules that exhibit solvatochromism and aggregation-induced emission enhancement (AIEE) phenomena. The application of PQCs for live cell imaging has also been demonstrated.
Keywords: Cell imaging; Dyes/pigments; fluorescence; Gold; Luminescence; Solvatochromism

Investigation of the biocompatibility and cytotoxicity associated with ROP initiator and its role in bulk polymerization of L-lactide - Parwe, Sharad P.; Warkad, Shrikant D.; Mane, Manoj V.; Shedage, Pranita S.; Garnaik, Baijayantimala (Polymer, 2017)
Poly (L-lactide) (PLLA) is one of the most attractive polymers for use in biomedical applications. In such applications it is necessary to reduce the use of toxic chemicals and catalysts used in PLLA synthesis, to minimize any adverse effects. In view of this, we have performed ring opening polymerization (ROP) of Llactide (LA) using biocompatible initiator, namely, Zinc L-Proline (ZnP) in bulk. High molecular weight PLLA (Mw up to 1.45 x 10(5) Da) was obtained using the ZnP complex. The ZnP complex is safe, easy to prepare, store and handle. H-1 and C-13 NMR spectra of PLLA were used to determine the extent of monomer conversion and stereo sequence respectively. Differential Scanning Calorimetry (DSC) and Size Exclusion Chromatography (SEC) were used to determine thermal properties, Mn, Mw and polydispersity index respectively. The mechanism of ROP of LA in the presence of ZnP was studied using Density Functional Theory (DFf) which was in good agreement with results from H-1 NMR and Matrix-Assisted Laser Desorption/Ionization Spectrometry (MALDI-TOF). Biocompatibility/non toxicity of PLLA prepared using ZnP was studied in-vitro using MTT assay by examining the proliferation rate of mouse myoblast C2C12 cell line. Escherichia coli and Staphylococcus aureus were used for the study of antibacterial activity of PLLA. (C) 2017 Elsevier Ltd. All rights reserved.